Control interno de procesos contables en el Gobierno Autónomo Descentralizado Parroquial Rural de La Unión De Clementina Periodo 2021. - Arana Avilés, Alba Hayly (2022)
The present case study is called as internal control of accounting processes was carried out in the Rural Parish Decentralized Autonomous Government of La Unión de Clementina, the objective for which this study was carried out was to examine the internal control procedures of the accounting processes that are carried out in said institution, by identifying, analyzing and measuring risks. The line of research with which it is directed is Financial, Tax, Audit and Control Management and in turn is jointly related to the Audit and Control sub-line. The methodologies used were qualitative and analytical, the techniques used were observation and a questionnaire to achieve the fulfillment of the objectives set. The results and the discussion of the results are given at the end of the investigation, which include the information obtained by the company that supports the work, where it was determined what the accounting processes were, in addition to the level of risk and confidence that these have.